A GIS-based modified frequency ratio model for gold potential mapping in Kelantan Malaysia - S. Aliyu , N.; A. Adebisi , M.; J. Ataman , O.; Mathew, T.; Suleiman, O. (International Journal of Advanced Geosciences, 2023)
Mineral system factors control the distributions of orogenic gold deposits in our immediate geological environment. The spatial knowledge of the relationship between the mineral factors and the gold deposits are crucial to locating these deposits in the environment. However, there is a current challenge in understanding the spatial correlation between ore genesis factors and orogenic deposits. Our paper analysed the spatial relationship between ore controlling factors and orogenic gold deposits in the Gua Musang area Kelantan, Malaysia. The procedure applied a modified frequency ratio model (MFR) to generate the gold potential map of the study area. The model relied on the spatial distribution of known gold deposits to predict new ones. Eight (8) known gold deposits and five (5) selected factors were used in the analysis. These factors include NE-SW lineaments, NW-SE lineament, host rock, heat source, alteration of iron and clay. The new findings show the factor with the highest predicting rate (Lineaments NE-SW) as the major gold deposits distribution factors within the study area. The created map highlight both known and new deposit locations. The area under curved (AUC) statistical graphs were used for the accuracy test. The results show 92.50% accuracy; thus, the approach is adaptable for gold mapping in Malaysia.